2020
DOI: 10.1097/mat.0000000000001189
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Angiopoietin-2 Before and After Mechanical Circulatory Support Therapy

Abstract: Gastrointestinal bleeding (GIB) during mechanical circulatory support (MCS) is a major unsolved comorbidity. Inadequate activation of angiopoietin-2-related systems is considered as a major cause of GIB. However, the regulation of angiopoietin-2 remains unknown. Consecutive 20 patients who received continuous-flow MCS therapy (MCS group) and 12 with advanced heart failure (HF; HF group) were prospectively enrolled and their angiopoetin-2 levels were compared. Angiopoietin-2 level had a moderate correlation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This might be the most common cause of LVAD-related gastrointestinal bleeding, as opposed to polyps or gastrointestinal mucosal ulceration [27,28]. It is plausible that abnormal hemodynamics, particularly systemic congestion due to elevated central venous pressures, are associated with the activation of these systems ( Figure 3) [29]. Recently, therapies including omega-3 fatty acid and digoxin administration were found to be associated with fewer gastrointestinal bleeding events, possibly due to suppression of these maladaptive cascades [30][31][32].…”
Section: Gastrointestinal Bleedingmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be the most common cause of LVAD-related gastrointestinal bleeding, as opposed to polyps or gastrointestinal mucosal ulceration [27,28]. It is plausible that abnormal hemodynamics, particularly systemic congestion due to elevated central venous pressures, are associated with the activation of these systems ( Figure 3) [29]. Recently, therapies including omega-3 fatty acid and digoxin administration were found to be associated with fewer gastrointestinal bleeding events, possibly due to suppression of these maladaptive cascades [30][31][32].…”
Section: Gastrointestinal Bleedingmentioning
confidence: 99%
“…Furthermore, abnormal hemodynamics, particularly right heart failure with elevated central venous pressure, may increase the risk of incident stroke (Figure 3) [13]. We postulate that an inflammatory cascade activates due to chronic and systemic congestion which may, in turn, increase cerebral vasculature vulnerability and the potential risk of stroke [29]. Another explanation may be a decrease in blood flow through the device because of impaired right ventricular function, contributing to increased stasis of flow and potentially increased risk of clot formation in the device [11].…”
Section: Strokementioning
confidence: 99%
“…The inflammatory system has a considerable association with advanced heart failure: Ang-2 and BNP have a strong correlation in the heart failure cohort. 5 Our team recently demonstrated that Ang-2 was inappropriately elevated relative to the BNP level during LVAD supports compared to the heart failure cohort, 4 probably due to the stimulation of Ang-2 activity via hematological instability. 6 This is a rationale of why we used Ang-2/BNP as a variable instead of Ang-2 alone.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Furthermore, Ang-2 is inappropriately elevated relative to BNP levels in some LVAD patients. 4 However, its prognostic impact on HRAEs remains uninvestigated. In this study, we investigated the prognostic impact of Ang-2 level relative to BNP (Ang-2/BNP) obtained immediately after percutaneous LVAD implantation on future occurrences of HRAE.…”
Section: Introductionmentioning
confidence: 99%
“…Data of biomarkers associating with the formation of arteriovenous malformation including angiotensin-2 might approach their findings. 3 Post-LVAD therapeutic data including antiplatelet and anticoagulant would also useful to establish an optimal strategy for those with malignancy.…”
mentioning
confidence: 99%